THE EFFECT OF USING TEAM-ASSISTED INDIVIDUALIZATION (TAI) METHOD ON STUDENTS ACHIEVEMT IN WRITING DESCRIPTIVE TEXT - Mhd. Teguh Priyono; Masitowarni Siregar; Nora Ronita Dewi (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study was aimed to find out the effect of  Team  Assisted Individualization (TAI) method on students’ achievement in writing descriptive text. It was conducted by using experimental research design. The population of this research was the first (X) grade students of SMA Al-Hidayah Medan. It consisted of  104 students with 3 parallel classes. Students were chosen as the sample by using random sampling technique. There were two randomized groups, namely experimental group and control group. Class X-1 with 36 students became the experimental group while class X-2 with 36 students became control group. The Experimental group was taught by using Team Assisted Individualization (TAI) method and the control group was taught without a treatment. The instrument which was used for collecting the data was writing test. The data was analyzed by using t-test formula. The result showed that the mean of score in post-test for experimental group ( 68.48) ) was higher than control group (66.53). The value of tobserved (2.94) is higher than the value of ttable (1.994) (a = 0.05 ) with the degree of freedom (df) = 70. So, alternative hypotheis (Ha) was accepted and the Team Assisted Individualization (TAI) method significantly affected students’ achievement in writing descriptive text. Keywords : Team-Assisted Indiividualization, Writing Descriptive Text